UTILIZATION OF ACTIVATED CHARCOAL FROM NUTMEG SHELL WASTE AS AN ADSORBENT TO IMPROVE THE QUALITY OF VIRGIN COCONUT OIL (VCO) FERMENTATION METHOD - Hitijahubessy, Hendro; Huwae, Laury Marcia Ch (Pattimura University, 2021)
Virgin coconut oil (VCO) is a form of processed coconut that is widely produced by people in Indonesia. VCO is often called pure coconut oil. VCO with good quality is by fermentation method using yeast. The quality of VCO can be measured by 3 types of analysis: water content, free fatty acids and peroxide number. The results of this analysis will be compared with the standards of the Asian and Pacific Coconut Community (APCC). VCO from fermentation method will be combined with the absorption method using nutmeg shell activated charcoal to see if there is a much better quality improvement. The results showed that there was a significant increase in quality with a decrease in the average water content from 0,1665% to 0,1005%. In addition, there was a significant decrease in the average free fatty acid content from 0,4681% to 0,3790% and significant decrease in average peroxide number from 0,1991 meq/kg to 0,0997 meq/kg. The results of the research on three VCO quality standards showed a value that was in accordance with the APCC standard.